Anti-interference algorithm of wireless channel for IoT communication - Ling TAN; Yong ZHUANG (Dianxin kexue)
In IoT communication,the anti-interference of wireless channel is influenced by various factors.Multi-antenna system has significant effect for promoting anti-interference of channel,whose complexity and performance in signal detection need further improvement.The QR decomposition detection algorithm in signal detection of multi-antenna system has low computational complexity,but the algorithm performance is poor.In order to improve the performance of QR decomposition detection algorithm,a QR decomposition algorithm based on ML criterion and decision candidate mechanism was proposed,and the performance of the algorithm was analyzed.The ML criterion was used to estimate the initial level of the detection,and a reliable decision was adopted in the other detection layer.Candidate points were introduced in unreliable case and the optimal candidate were selected from the feedback.The algorithm could significantly improve the system interference,and propagation error were greatly reduced in the decision feedback.The experimental results show that the proposed algorithm can improve the performance of the IoT system effectively with certain complexity.